Comparison between Land Surface Temperature and UAV Thermal Imaging to Analyze Urban Heat Island Phenomenon in Pasar Besar Corridor, Malang City - Widastri, Amanda Rahmat; Hasyim, Abdul Wahid; Agustin, Imma Widyawati (Civil and Environmental Science Journal (CIVENSE), 2025)
The urban heat island (UHI) phenomenon has been detected in Malang City, defined as an urban area with a higher surface temperature than its surrounding areas. Pasar Besar Corridor is the center of trade and services as well as the Central Business District (CBD) of Malang City, located in Sukoharjo Sub-District, Klojen District. Although it is an economically strategic area in Malang City, Pasar Besar Corridor is vulnerable to high-intensity UHI exposure, so it is necessary to conduct a study related to the UHI phenomenon. This research aims to compare the results of UHI analysis between macro-scale and micro-scale analysis. Macro-scale UHI analysis was performed using Landsat-8 data as input for Land Surface Temperature (LST), while micro-scale UHI analysis utilized UAV thermal imaging. The results of the analysis show that while Pasar Besar Corridor is not considered a hot spot in Sukoharjo Village at the macro-scale level, a micro-scale UHI has occurred in Pasar Besar Corridor, with the roads being the hot spot, or “heat islands," reaching 48.62 °C. There is a significant difference between the highest temperature from UAV thermal imaging and LST, caused by the differences in resolution and altitude between Landsat-8 data and UAV data. From this research, it is concluded that LST is more suitable for larger study areas, while UAV thermal imaging is better suited for small-scale and more detailed analysis. However, each tool has its limitations, such as lower detailed accuracy for LST and higher costs for UAV thermal imaging.